Stilbenes: a promising small molecule modulator for epigenetic regulation in human diseases - Tian, Jing; Jin, Li; Liu, Hongquan; Hua, Zichun (Frontiers in Pharmacology, 2023)
Stilbenes are characterized by a vinyl group connecting two benzene rings to form the basic parent nucleus. Hydrogen atoms on different positions of the benzene rings can be substituted with hydroQxyl groups. These unique structural features confer anti-inflammatory, antibacterial, antiviral, antioxidant, anticancer, cardiovascular protective, and neuroprotective pharmacological effects upon these compounds. Numerous small molecule compounds have demonstrated these pharmacological activities in recent years, including Resveratrol, and Pterostilbene, etc. Tamoxifen and Raloxifene are FDA-approved commonly prescribed synthetic stilbene derivatives. The emphasis is on the potential of these small molecules and their structural derivatives as epigenetic regulators in various diseases. Stilbenes have been shown to modulate epigenetic marks, such as DNA methylation and histone modification, which can alter gene expression patterns and contribute to disease development. This review will discuss the mechanisms by which stilbenes regulate epigenetic marks in various diseases, as well as clinical trials, with a focus on the potential of small molecule and their derivatives such as Resveratrol, Pterostilbene, and Tamoxifen.